Analysis of the Muscle Structure and Protein Composition of Different Varieties of Cultured Large Yellow Croaker (Larimichthys crocea) - Yuan MA; Quanyou GUO; Yao ZHENG; Weibo SUN; Liu YANG; Xiaoyan SONG (Shipin gongye ke-ji)
To investigate the differences in edible quality among different varieties of cultured large yellow croaker, this study focused on 'Donghai 1' 'Yongdai 1' 'Fufa 1' 'traditional Zhejiang variety', and 'traditional Ningde variety', analyzing their muscle structure and protein composition. Results showed certain differences in the basic nutritional composition among the various varieties. The crude protein content in the muscle of 'Fufa 1' was significantly higher than that of the other four varieties, while the 'traditional Zhejiang variety' had the lowest crude fat content, at only 2.77%. The muscle fiber density of 'Yongdai 1' was the highest, being 1.43 times that of the 'traditional Ningde variety'. The cross-sectional area of the muscle fibers of the five varieties ranked from largest to smallest as follows: 'traditional Zhejiang variety'>'traditional Ningde variety'>'Fufa 1'>'Donghai 1'>'Yongdai 1'. Low-field NMR also revealed that the immobile water in 'Yongdai 1' had a shorter relaxation time. The salt-soluble protein content in the muscle of 'Fufa 1' was the highest, being 1.29 times that of 'Donghai 1'. The water-soluble protein content among the five varieties ranged from 58.72 mg/g to 74.85 mg/g, while the electrophoresis results showed no differences in the muscle protein molecular weight distribution across different varieties. The leucine, lysine, phenylalanine, and tyrosine contents in the muscles of all five varieties were higher than the WHO/FAO standards. This study systematically analyzed the differences in muscle structure and protein composition among different varieties of cultured large yellow croaker from the perspective of food material, providing a reference for subsequent variety selection and high-quality processing.